PERAN PELATIHAN PUBLIC SPEAKING DALAM MENUMBUHKAN RASA PERCAYA DIRI SISWA DI DJ ARIE PUBLIC SPEAKING & BROADCASTING SCHOOL BANDUNG - Ayi Najmul Hidayat; Hasbullah lau (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2023)
This research was conducted at Dj Arie Public Speaking and Boardcasting School Bandung. The problem contained in the formulation of the problem is how the role of public speaking training in fostering student confidence at Dj Arie Public Speaking and Boardcasting School Bandung. The purpose of this study is to determine the role of public speaking training in fostering student confidence at Dj Arie Public Speaking and Boardcasting School Bandung. This research uses qualitative methods and is a field research. The research data was obtained through direct observation to the field, interviews involving students and tutors who became informants, and documentation studies from books and other materials related to the subject matter. The results of this study indicate that the role of public speaking training is very large in fostering students' confidence which is one of the supports and provisions when speaking in public such as appearing at events and can be a provision for students in carrying out certain public speaking activities.